Perpustakaan maya sebagai sumber belajar dan penunjang pembelajaran IPS secara daring di era pandemi COVID-19 - Mochamad Doni Akviansah; Sariyatun Sariyatun (Universitas Negeri Malang, 2020)
This article aimed to describe how important the existence of virtual libraries is as a learning resource in online social studies learning, because virtual libraries provide the widest possible access by anyone, anywhere, anytime to dig up various information that can later be used by students, educators, and even. The principal of this study utilized descriptive qualitative research methods. This research was motivated by the emergence of the Covid-19 outbreak which resulted in many changes and technological developments that drove the comprehensive digitization process. The conditions during a pandemic by requiring online learning are the route chosen to keep the education system running. The role of technology is very visible and very impactful in times like this. In addition to the human resources and supporting technology that are prepared, the components in learning must also be prepared to support learning online. One of these components is a virtual library that is easy to use and useful as a learning resource and learning support. In addition, virtual libraries can improve students' abilities in terms of reading so that they can increase knowledge which has an impact on increasing student achievement. DOI: http://dx.doi.org/10.17977/um022v5i22020p92